2019
DOI: 10.1098/rspa.2019.0371
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial acoustic waves in one-dimensional anisotropic phononic bicrystals with a symmetric unit cell

Abstract: The paper is concerned with the interfacial acoustic waves localized at the internal boundary of two different perfectly bonded semi-infinite one-dimensional phononic crystals represented by periodically layered or functionally graded elastic structures. The unit cell is assumed symmetric relative to its midplane, whereas the constituent materials may be of arbitrary anisotropy. The issue of the maximum possible number of interfacial waves per full stop band of a phononic bicrystal is investigated. It is prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…are × 3 3 matrices whose columns A and L are the first three and second three components of = A L ( ) T , respectively. It is at this stage that the case of superlattices with a symmetric unit cell studied in [34] diverges from the present general consideration. By symmetric we mean the unit cells whose arrangement is invariant relative to the midplane.…”
Section: Transfer Matrixmentioning
confidence: 57%
See 3 more Smart Citations
“…are × 3 3 matrices whose columns A and L are the first three and second three components of = A L ( ) T , respectively. It is at this stage that the case of superlattices with a symmetric unit cell studied in [34] diverges from the present general consideration. By symmetric we mean the unit cells whose arrangement is invariant relative to the midplane.…”
Section: Transfer Matrixmentioning
confidence: 57%
“…It is found that a bicrystal with any asymmetric unit cells admits up to three interfacial waves in the lowest and up to six waves in any upper stopband. This is in contrast to at most one and three waves which may exist in the lowest and upper stopbands of a bicrystal with both halves having a symmetric unit cell [34]. Moreover, the aforementioned bound, which is three or six waves per stopband, is shown to actually be the maximum for the total number of waves occurring per the same stopband in a given bicrystal and in the "complementary" bicrystal, which is obtained by swapping upper and lower superlattices of the initial one.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The majority of the authors were fortunate to have enjoyed collaborations and interactions with Peter in various capacities. The papers by Barnett [2], Darinskii & Shuvalov [3] and Fu et al . [4] are in the area of Peter's primary research interest related to the most general treatment of surface and interfacial waves.…”
mentioning
confidence: 99%